2019
DOI: 10.1093/nar/gkz848
|View full text |Cite
|
Sign up to set email alerts
|

PhaSePro: the database of proteins driving liquid–liquid phase separation

Abstract: Membraneless organelles (MOs) are dynamic liquid condensates that host a variety of specific cellular processes, such as ribosome biogenesis or RNA degradation. MOs form through liquid–liquid phase separation (LLPS), a process that relies on multivalent weak interactions of the constituent proteins and other macromolecules. Since the first discoveries of certain proteins being able to drive LLPS, it emerged as a general mechanism for the effective organization of cellular space that is exploited in all kingdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(175 citation statements)
references
References 52 publications
3
172
0
Order By: Relevance
“…In human cells, Herpes Simplex Virus appears to share many properties commonly attributed to LLPS, but SPT measurements have recently shown that they are formed through a distinct compartmentalization mechanism 54 . As the list of proteins that can undergo phase separation is growing in the literature 56,57 , it will be essential to confirm the nature of sub-compartments using in vivo single molecule approaches. It also becomes necessary to define solid criteria and observables at the microscopic level to distinguish between different models (Heltberg et al, in preparation) and to develop alternative models of membrane-less sub-compartments.…”
Section: Working Model For Rad52 Focimentioning
confidence: 99%
“…In human cells, Herpes Simplex Virus appears to share many properties commonly attributed to LLPS, but SPT measurements have recently shown that they are formed through a distinct compartmentalization mechanism 54 . As the list of proteins that can undergo phase separation is growing in the literature 56,57 , it will be essential to confirm the nature of sub-compartments using in vivo single molecule approaches. It also becomes necessary to define solid criteria and observables at the microscopic level to distinguish between different models (Heltberg et al, in preparation) and to develop alternative models of membrane-less sub-compartments.…”
Section: Working Model For Rad52 Focimentioning
confidence: 99%
“…As this interaction is crucial for LLPS, only short SynGAP isoforms can form MLOs. Similar motif–domain interactions are common in LLPS , and AS has been shown to specifically target them in several cases, such as GRB2, a component of the phase‐separated LAT signalosome . The short isoform, called GRB3‐3, lacks a functional SH2 domain, inhibiting the binding of phosphorylated Tyr crucial for signalosome formation with LAT .…”
Section: Phase Separation and Alternative Splicingmentioning
confidence: 87%
“…A large number of studies have addressed the identity of constituent proteins (and RNA), the conditions of the formation of MLOs and their physical properties. As a result, many ‘phase‐separating’ proteins have been identified, ranging from 120 (PhaSePro ) to 9300 (DrLLPS ). These contradicting numbers raise the issue of specificity and probably highlight the fact that only a small fraction of phase‐separating proteins (scaffolds) actually drive phase separation, while many of them (clients) only get recruited into the droplets once they have formed .…”
Section: Introduction: Why Llps Needs To Be Regulatedmentioning
confidence: 99%
“…Further, protein kinase C βII-induced upregulation and mitochondrial translocation of the adaptor protein, p66SHC, was associated with the formation of hyperglycemic molecular memory of human aortic endothelial cells ( Figure 2 [30]). Protein translocation may also occur between subcompartments of a cellular organelle, such as in the nucleus or in the form of the formation of biomolecular condensates by liquid-liquid phase separation [31]. Protein translocation establishes a whole set of novel protein-protein interactions, increasing their edge weights in signaling networks.…”
Section: Subcellular Protein Translocationmentioning
confidence: 99%